Strategic foresight in the luxury industry: managerial perspectives. (2015) - Berghaus, Benjamin; Bossard, Chiara; Baehni, Laure-Line
Luxury brands position themselves on creating offers created through unique savoir-faire. This positioning is commonly supported by substantial brand heritage. However, the ubiquity of heritage as a guiding compass to developing luxury brands leads to a new paradox: how does the notoriously heritage-conscious luxury industry deal with planning ahead? After all, today's luxury industry is not only an ever changing, ever more competitive environment - it is driven by consumer behaviour following the slightest changes in values and consumer culture. A lack of strategic foresight in such a volatile market might leave prestigious brands stranded missing critical turns of the market. In this study, we explored luxury executives' perceptions on strategic foresight. We identified five central factors that determine the degree of managerial engagement in strategic foresight. Moreover, we found three distinct perspectives based on different business sizes and ownership structures. Finally, we integrated our findings and outline a pragmatic research agenda.